PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MENGGUNAKAN METODE MIND MAP - Susanti, Herlin (sarasvati, 2021)
This research was conducted to improve the skills of writing descriptive texts through the mind map method of class VII-C students of SMP Muhammadiyah 9 Bojonegoro in the 2020/2021 school year. The type of research used in this research is Classroom Action Research (CAR), which means that this research is in the form of reflective research by taking certain actions in order to improve and / or improve learning practices in the classroom professionally. Therefore, CAR is expected to improve the quality of learning and be successful. The implementation of learning to write descriptive text using the mind map method can work well. This can be seen from the results of observing student activity in cycle I, as many as 14 students did learning activities very well, 7 students did learning activities well, 4 students did activities quite well, and 2 students did activities poorly, while in cycle II, as many as 14 students did learning activities very well, 9 students did learning activities well, 4 students did activities quite well. In cycle II, there were no students who did learning activities poorly so that there was an increase in learning activities for the better. In addition, the results of the observation of the value of students' attitudes in cycle I obtained data as many as 13 students who had very good attitudes, 7 students had good attitudes, 5 students had sufficient attitudes, and 2 students had less attitudes in following the learning process. This result is categorized as good, while in cycle II, as many as 13 students had a very good attitude, 11 students had a good attitude, and 3 students had sufficient attitudes in following the learning process and this result was categorized as very good because there was an increase from the previous cycle.